Political Economy of the Digital Economy - Prodanov, Hristo (Research Papers, 2020)
This study aims to analyze the consequences of the large scale transformation that occurs in the contemporary societies as a result of the ongoing transition to digital economy. The approach in this sense is politico-economic, grounded on the ideas of the classical political economy, which examines the economic cycle of the various categories of production, exchange, distribution and consumption, considering that in this process people enter into certain relationships that are regulated by politics. At the same time the approach considers that politico-economic system is not static, but in the process of evolution and transformation. Because of this evolution the digital economy brings many new features to the politico-economic system and this imposes the need of new and different approaches and paradigms. This research is the first comprehensive attempt to discover the essential changes in the economic cycle, different economic categories, and in political economy. The practical conclusions and proposals are related to the need of a large-scale and systematic transformation of the modern state, if it is to meet the growing challenges.